Stable isotopes and radiocarbon measurements of sediment core MD99-2220 - Anne de Vernal; Claude Hillaire-Marcel; Guillaume St-Onge; Xiner Wu (PANGAEA, 2023)
The 51.58 m long marine sediment core MD99-2220 was raised from the Laurentian Channel in the St. Lawrence Estuary during the IMAGES-V (International Marine Past Global Change Study) oceanographic expedition, in July 1999, on board the Marion Dufresne II, using the Calypso piston corer. It provided very high-resolution records of middle to late Holocene paleoceanography changes (e.g., de Vernal et al., 2011) and a reference paleomagnetic record (St-Onge et al., 2003). After splitting, the sediment core has been subsampled at 1-cm interval and analyzed at the Geotop-UQAM Research Center. The volume of wet sediment subsamples was measured by water displacement. Subsamples were weighed, then air-dried and weighed again. Percentages of organic carbon and calcium carbonate were measured by Coulometer. Samples for geochemical analysis were dried at 60°C and then ground to fine powder using an agate mortar. Total carbon and nitrogen measurements were performed on ground aliquots, using a Carlo-Erba™ elemental analyzer. Another aliquot was then acidified twice with HCl (1 M) to remove carbonates, washed, dried, and divided into two portions for stable isotope analysis and determination of residual carbon content, considered to represent the organic carbon (OC) fraction. OC and N contents are expressed in dry weight percent of total sediment. Uncertainties, as determined from replicate measurements of standard substances, are estimated to average ±5% relative for OC and N contents. Aliquots for isotopic analysis were combusted in a quartz tube for 1 h at 850°C in the presence of purified cupric oxide wire and high-quality granular copper (e.g., Macko, 1981). The gases were then analyzed on a VG-PRISM™ instrument. Isotope data of OC and N are reported in δ extperthousand values, after usual corrections (Craig, 1965), and with reference to V-PDB (Coplen, 1996), and atmospheric N, respectively. Uncertainties were lower than ±0.1 extperthousand, as determined from routine replicate measurements of standards. Whenever present, tests of the benthic foraminifera Globobulimina auriculata were hand-picked from the 125–250 μm fraction for δ18O and δ13C analyses. CO2 was extracted at 90°C using an ISOCARB™ device on-line with a VG-PRISM™ mass spectrometer. All measurements were made using an in-house standard marble calibrated against the Carrara marble and other current standard materials of the International Atomic Energy Agency of Vienna. Results were converted to the VPDB scale (Coplen 1996) after usual corrections (Craig 1957). The overall analytical reproducibility, as determined from replicate measurements on the in-house standard material, was routinely better than ±0.05 extperthousand (±σ) for both δ13C and δ18O. Mollusk shell fragments were handpicked for AMS 14C dating at the Isotrace Radiocarbon Laboratory of the University of Toronto.